OXYGEN ISOTOPE VARIATIONS OF BASALTIC LAVAS AND UPPER MANTLE ROCKS - Eiler J.M. (My University, 2001)
This chapter summarizes the oxygen isotope geochemistry of terrestrial basalts and their mantle sources, including the conceptual framework for interpreting such data and the phenomenology of known variations. In particular, the first section outlines the motivations for and first-order results of oxygen isotope studies of terrestrial and lunar basalts over the last 30 years; the second section reviews oxygen isotopic fractionations among phases relevant for studying basalts and mantle rocks; the third summarizes variations in δ18 O of various crustal rocks that may contribute to the petrogenesis of basalts either as subducted source components or lithospheric contaminants; and the final and longest section describes observed oxygen isotope variations of major classes of terrestrial basalts and related mantle nodules with an emphasis on data generated within the last six years using laser-based fluorination techniques.